Ethnogastronomic Insights into Indigenous Deep-fried Snack Foods of Northeast India: A Review of Traditional Knowledge Systems and Processing Practices - Apeksha,; , Sujata Jena; , Dhamchoe Dolma Bhutia (Archives of Current Research International, 2025)
Background: Traditional foods are integral to cultural identity and heritage, offering insights into regional diversity and culinary practices. In North East India, the rich tapestry of indigenous snacks reflects the region's unique geographical and climatic conditions. These snacks, primarily cereal-based and often deep-fried, include items like Sel roti, Zhero (Sikkim), Pukhein (Meghalaya), Khapse (Arunachal Pradesh), and Kakching Bora (Manipur). Steamed varieties such as pithas and pusyep are also prevalent. Despite their cultural significance, traditional production methods for these snacks are time-consuming, labor-intensive, and result in product non-uniformity. Objective: This study aims to explore and document indigenous knowledge related to the traditional processes of snack production in North East India. It seeks to identify gaps in standardization and propose modern technological interventions to enhance production efficiency, product consistency, and shelf life. Methods: A comprehensive review of existing literature was conducted to understand traditional snack preparation methods. Field visits were undertaken to engage with local producers and gather firsthand insights into raw material selection, processing techniques, and packaging practices. Additionally, consultations with food technologists were held to assess the feasibility of integrating contemporary technologies into traditional practices. Results: The study identified several challenges in traditional snack production, including variability in taste and texture, inconsistent product sizes, and limited shelf life. However, it also highlighted the potential for improvement through the adoption of modern technologies such as standardized cooking equipment, automated frying processes, and advanced packaging materials. Conclusions: Integrating contemporary food processing technologies with traditional methods can significantly enhance the quality, consistency, and shelf life of indigenous snacks from North East India. This fusion not only preserves cultural heritage but also opens avenues for commercial viability and broader market reach. Further research and development are recommended to tailor technological solutions that align with local practices and resources.